Transgression et subversion : George Jacob Holyoake, Charles Bradlaugh et l’athéisme militant à l’époque victorienne - Jean-Michel Yvard (Cahiers Victoriens et Edouardiens)
In the Victorian period, atheism was certainly one of the most transgressive, politically incorrect intellectual positions that were professed. Not only did it have a theological dimension, but it also had major ethical and social implications that still made it rather uncommon at the time, particularly in the context of the renewal of faith that had been induced by evangelical forms of spirituality since the 18th century. This position was perceived as violating both the norms of the proper conduct of reason as well as those of virtuous action. Even if the idea of ‘honest doubt’ had been gradually making its way, the reputation of the atheist was still mainly negative. Charles Bradlaugh (1833-1891), who became the most famous representative of atheism at the time, embodied both the intellectual debate induced by the question of the existence of God and a constant, militant involvement in favour of other causes that were just as radical and transgressive, such as republicanism or artificial birth control. In 1880, when he became an MP, Bradlaugh never stopped professing an atheistic position, which prevented him from occupying his seat in the House of Commons for six years, although he was later re-elected no less than four times. In 1888, he passed a law that enabled future MP’s to take a non-religious oath. This article explores the ideological impact of Bradlaugh’s intellectual evolution, as well as that of his predecessor George Jacob Holyoake.